2023
DOI: 10.3390/jcm12031199
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 and Chronic Kidney Disease: A Meta-Analysis

Abstract: Oxidative stress is known to be associated with the pathophysiology of chronic kidney disease (CKD). Paraoxonase 1 (PON1) is an antioxidant enzyme that has been proposed as a biomarker for CKD. While several studies have reported an association between serum PON1 activity and CKD, consensus based on systematically analyzed data remains necessary. We set out to conduct a meta-analysis of literature on PON1 in CKD. Electronic databases, such as MEDLINE, Embase and CENTRAL, were searched for available studies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…The network meta-analysis of arylesterase activity was performed in 22 studies. Healthy controls had higher activity relative to CRF patients in agreement with the previous report [7]. Arylesterase activity was significantly higher in CRF patients with RTx (SMD 1.84; 95% CI, 0.18-3.50) compared to those without RRT.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The network meta-analysis of arylesterase activity was performed in 22 studies. Healthy controls had higher activity relative to CRF patients in agreement with the previous report [7]. Arylesterase activity was significantly higher in CRF patients with RTx (SMD 1.84; 95% CI, 0.18-3.50) compared to those without RRT.…”
Section: Resultssupporting
confidence: 91%
“…Given the importance of PON1 for CVD in CRF patients with RRT, the present comprehensive meta-analysis of studies was carried out to assess the effect of various RRT types on PON1 activity [2,4,6]. The analysis corroborated the earlier finding that healthy controls have higher PON1 activities than CFK patients [7]. Importantly, we observed that paraoxonase and arylesterase activities were highest in CRF patients receiving RTx, followed by higher activity levels in patients under HD and PD as compared to those not receiving RRT.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Importantly, the serum protein–metabolite interactions that annotated in our integrated analysis revealed a larger network encompassing other components associated with clinical complications of ESKD. For instance, meta-analysis revealed that serum paraoxonase 1 (PON1) activity is likely reduced in CKD (decreased level shown in Figure 5C ), suggesting the antioxidant defense is impaired ( Watanabe et al, 2023 ). The beneficial role of PON1 activity on reducing the cardiovascular event has been reported ( Shih and Lusis, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…A high-density lipoprotein (HDL)-associated esterase called paraoxonase 1 (PON1), which is also known as arylesterase and paraoxonase (depending on the substrate employed in its measurement), inhibits the buildup of lipid peroxide on low-density lipoprotein, and low PON1 activity can raise the risk of cardiovascular events [ 5 , 6 ]. In addition, PON1 has been proposed as an antioxidant biomarker for monitoring CKD [ 7 ].…”
mentioning
confidence: 99%